Effect of hydrotherapy on recovery of muscle-damage and exercise-induced fatigue - Vaile, J. (2008)
Achieving adequate and appropriate recovery from exercise is essential in ensuring optimal performance during repeated bouts of exercise. The use of various recovery interventions has become popular in an attempt to enhance subsequent performance and accelerate post-exercise recovery. The application of various post-exercise hydrotherapy interventions has become increasingly popular, however, the majority of current recovery practices appear to be based largely on anecdotal evidence as opposed to rigorous scientific research or evidence based findings. Physiologically, various hydrotherapy protocols have been shown to affect the body via fluid shifts (interstitial to intravascular space), changes in blood flow and cardiovascular function, and reductions in oedema. The possible psychological effects of water immersion must also be considered, with athletes commonly reporting reduced sensations of fatigue and soreness following immersion. Current literature suggests both hydrostatic pressure and water temperature to be important factors influencing the success of hydrotherapy. The overall aim of the present thesis was to enhance current knowledge and understanding with regards to the physiological and performance effects of various forms of hydrotherapy, used as a post-exercise recovery intervention. Initially, four cold water immersion interventions were compared to active recovery, performed between two bouts of high intensity cycling in hot environmental conditions. Effectiveness of recovery was determined via performance in a subsequent exercise bout; in addition, core body temperature, lactate, and heart rate were recorded. The remaining studies were designed to investigate the effects of cold water immersion, hot water immersion, contrast water therapy, and passive recovery 4 (control) following exercise-induced fatigue and exercise-induced muscle damage. Rate of recovery was assessed through changes in performance, core body temperature, thigh girths, blood markers, and perceived exertion/soreness. The results of the combined studies indicate cold water immersion to be more effective than active recovery when performed immediately post-exercise between two bouts of high intensity cycling in hot environmental conditions. Additionally, both cold water immersion and contrast water therapy were effective in aiding recovery from exercise-induced fatigue and exercise-induced muscle damage. Performance variables indicated an improved maintenance or return of performance following these recovery protocols. The present studies have provided additional information to the limited knowledge base regarding the effect of post-exercise hydrotherapy interventions, specifically, the effect of such interventions on subsequent athletic performance. In conclusion, cold water immersion and contrast water therapy appear to be superior to hot water immersion, active recovery, and passive recovery following fatiguing and muscle damaging exercise. Functional and physiological recovery was enhanced following the use of these two recovery protocols.